Penerapan Pengaruh Terapi Murottal Surat Ar Rahman terhadap Status Hemodinamik pada Pasien Rawat Inap di Ruang ICU (Intensive Care Unit) RSUD Dr. Soehadi Prijonegoro Sragen - Angelia Aprilliani; Ika Silvitasari; Yani Indrastuti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Intensive Care Unit (ICU) is a special room for patients who are critically ill to receive special medical and nursing services in a hospital. This is associated with several conditions and situations, for example heart disease and other conditions that affect the heart can cause hemodynamic instability. An unstable hemodynamic condition carries a high risk of potential complications that can cause death. Non-pharmacological therapy to reduce hemodynamic status is by using Murottal Surah Ar-Rahman therapy. To find out the results of applying the effect of Murottal Surah Ar Rahman therapy on hemodynamic status in inpatients in the ICU (Intensive Care Unit) RSUD dr. Soehadi Prijonegoro Sragen. The design used was qualitative with descriptive methods using pre-test and post-test case studies, the application of therapy was carried out 3 days for 16 minutes on 2 respondents. Based on the results of the implementation, there was a decrease in hemodynamic status after Murottal Surat Ar Rahman Therapy was carried out. Murottal Surat Ar Rahman therapy can be used as a non-pharmacological technique or independent intervention in patients with inpatient hemodynamic status